2020
DOI: 10.2196/21983
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for the Prediction of Helicobacter Pylori Infection in Endoscopic Images: Systematic Review and Meta-Analysis Of Diagnostic Test Accuracy

Abstract: Background Helicobacter pylori plays a central role in the development of gastric cancer, and prediction of H pylori infection by visual inspection of the gastric mucosa is an important function of endoscopy. However, there are currently no established methods of optical diagnosis of H pylori infection using endoscopic images. Definitive diagnosis requires endoscopic biopsy. Artificial intelligence (AI) has been increasingly adopted in clinical practice, especially for image recognition and classif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 35 publications
0
43
0
1
Order By: Relevance
“…This method demonstrated to improve the accuracy and productivity of endoscopic examination, with respect to WLI, with a sensitivity for BLI-bright and for LCI of 96.7% [ 33 ]. In a recent meta-analysis, the artificial intelligence algorithm demonstrated to be an accurate tool for the prediction of H. pylori infection during endoscopic procedures, although, the authors concluded that the real application needs to be evaluated in clinical studies [ 34 ]. Figure 1 shows some gastric mucosa features associated with H. pylori infection in different studies.…”
Section: Invasive Testsmentioning
confidence: 99%
“…This method demonstrated to improve the accuracy and productivity of endoscopic examination, with respect to WLI, with a sensitivity for BLI-bright and for LCI of 96.7% [ 33 ]. In a recent meta-analysis, the artificial intelligence algorithm demonstrated to be an accurate tool for the prediction of H. pylori infection during endoscopic procedures, although, the authors concluded that the real application needs to be evaluated in clinical studies [ 34 ]. Figure 1 shows some gastric mucosa features associated with H. pylori infection in different studies.…”
Section: Invasive Testsmentioning
confidence: 99%
“…This highlights not only the importance of robust answers provided by the AI but also the importance of the baseline level of experience of AI users. Therefore, the conclusion from the previous study [6] that inexperienced doctors would benefit the most from AI support was not reproduced in this study. Rather, endoscopists having at least a certain level of expertise benefited from AI support.…”
Section: Discussionmentioning
confidence: 73%
“…Artificial intelligence (AI) using deep learning (DL), which mimics the intellectual function of humans, has been increasingly adopted in clinical medicine, especially for cognitive function in computer vision [1][2][3], including automated image recognition, classification, and segmentation tasks [4][5][6]. Application of AI to endoscopic examination is noninvasive and can further help in detecting hidden or hard-to-detect lesions in real time.…”
Section: Introductionmentioning
confidence: 99%
“…One meta-analysis including 8 studies and 1719 patients (385 patients with H. pylori infection vs. 1334 controls) diagnosed by WLI, BLI, or LCI reported that the sensitivity, specificity, DOR, and AUC of AI for the prediction of H. pylori infection were 0.87, 0.86, 40, and 0.92, respectively. The accuracy of the AI algorithm reached 82% for discrimination between noninfected images and posteradication images [87]. Regarding WLI, a DCNN model trained and verified by WLI of gastric antrum showed a power in diagnosing atrophic gastritis with 94% accuracy, 0.95 sensitivity, and 0.94 specificity, which were higher than those of experts [88], and AI diagnosis could be done in a considerably shorter time less than 200 s [89,90].…”
Section: Ai: One Of Present Advances In Endoscopic Diagnosis Of H Pylori Infectionmentioning
confidence: 94%